A failed model of development: The Argentine experience (1989-2001) - Gantman, Ernesto R. (Cuadernos de Relaciones Laborales, 2012)
This paper analyses the model of development adopted by the Menem Administration in Argentina, when a deep structural adjustment was carried out in order to reduce the State’s burden upon the economy While the results involved important negative social effects, particularly in terms of rising unemployment and social inequality, the economy experimented high growth rates during the period. However, the massive accumulation of external indebtedness precipitated the model’s collapse in 2001.
Keywords: neoliberalism; Argentina; economic development